The Complex Interplay between DNA Injury and Repair in Enzymatically Induced Mutagenesis and DNA Damage in B Lymphocytes - Bahjat, Mahnoush (Int J Mol Sci, 2017)
Lymphocytes are endowed with unique and specialized enzymatic mutagenic properties that allow them to diversify their antigen receptors, which are crucial sensors for pathogens and mediators of adaptive immunity. During lymphocyte development, the antigen receptors expressed by B and T lymphocytes are assembled in an antigen-independent fashion by ordered variable gene segment recombinations (V(D)J recombination), which is a highly ordered and regulated process that requires the recombination activating gene products 1 & 2 (RAG1, RAG2). Upon activation by antigen, B lymphocytes undergo additional diversifications of their immunoglobulin B-cell receptors. Enzymatically induced somatic hypermutation (SHM) and immunoglobulin class switch recombination (CSR) improves the affinity for antigen and shape the effector function of the humoral immune response, respectively. The activation-induced cytidine deaminase (AID) enzyme is crucial for both SHM and CSR. These processes have evolved to both utilize as well as evade different DNA repair and DNA damage response pathways. The delicate balance between enzymatic mutagenesis and DNA repair is crucial for effective immune responses and the maintenance of genomic integrity. Not surprisingly, disturbances in this balance are at the basis of lymphoid malignancies by provoking the formation of oncogenic mutations and chromosomal aberrations. In this review, we discuss recent mechanistic insight into the regulation of RAG1/2 and AID expression and activity in lymphocytes and the complex interplay between these mutagenic enzymes and DNA repair and DNA damage response pathways, focusing on the base excision repair and mismatch repair pathways. We discuss how disturbances of this interplay induce genomic instability and contribute to oncogenesis.